Women's Employment and Childcare Choices in Spain Through The Great Recession. Issue 2 (3rd April 2019) - Legazpe, Nuria; Davia, María A.
ABSTRACT: The Great Recession (2008–13) changed patterns in women's employment and the use of formal and informal external childcare among mothers of young children in Spain. This paper analyzes these changes using an analytical strategy that takes into account interdependencies across the outcomes under study. The results show that the economic crisis has resulted in interesting changes in the use of external childcare across mothers' and fathers' employment status; for example, as men's unemployment increased, the use of informal non-parental childcare declined, which might be related to (unobserved) changes in fathers' involvement in childcare during the recession. These results further indicate the need for policies that improve access to formal childcare, as well as policies that provide men and women with employment stability.